Penggunaan Laboratorium Virtual dan Teknologi Imersif dalam Pembelajaran Sains di Era Digital - Nurroniah, Novi Silvia; Farizi, Taufiq Al (Universitas Garut, 2024)
This study aims to explore the use of virtual laboratories and immersive technologies, such as Virtual Reality (VR) and Augmented Reality (AR), in science education in the digital era. These technologies are believed to enhance student engagement, facilitate the understanding of complex concepts, and overcome the limitations of physical laboratories. The study employed a Systematic Literature Review (SLR) method by analyzing 13 selected articles from 574 initially identified studies in the Scopus and Scimago databases, published between 2015 and 2025. The analysis involved thematic coding, synthesis of findings, and comparison of research results to identify the benefits, challenges, and implementation trends. The findings indicate that virtual laboratories and immersive technologies can increase learning motivation, provide safe and flexible experimental experiences, and deepen the understanding of scientific concepts. However, challenges such as limited infrastructure, high costs of equipment procurement, and the need for teacher training remain significant obstacles. This study concludes that integrating virtual laboratories and immersive technologies has great potential to enrich science learning but requires policy support, infrastructure development, and enhanced teacher competencies. The implications emphasize the need for collaboration among educational institutions, policymakers, and technology providers to optimize their application in science education.